The Implementation of Dictogloss Technique of Joox App to Improve Students Listening Skill - alifah ifa alifah (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2022)
This research is to find out the improvement of students’ listening skill using dictogloss technique with joox app at the eight grade of SMPN 1 Gunung Kaler. The research is conducted based on some problems: 1. How is the improvement of students’ listening skill before and after using dictogloss technique with joox app? 2. How is the effectiveness of using dictogloss technique with joox app? 3. How is students opinion after implementing using dictogloss technique with Joox app to improve listening skill? The researcher used a pre-experimental research design with use the instruments were three stages are pre-test, treatment and post-test. Population of the research was the eight grade of SMPN 1 Gunung Kaler, academic year 2021/2022. The sample of the research used class VIII A as experiment class from 27 students. The data analysis of this research used t-test.  The results of this study indicate the effect of implementation dictogloss Technique with Joox app effective for improving students' listening skill.  The effect of treatment is seen from the post-test results with a mean score of 78.9 with improvement 76.51%, which means that there is a significant effect of using dictogloss Technique with Joox app in improving students' listening skills.